An Open-Format Enteroid Culture System for Interrogation of Interactions Between Toxoplasma gondii and the Intestinal Epithelium - Luu, Lisa; Johnston, Luke J.; Derricott, Hayley; Armstrong, Stuart D.; Randle, Nadine; Hartley, Catherine S.; Duckworth, Carrie A.; Campbell, Barry J.; Wastling, Jonathan M.; Coombes, Janine L. (Frontiers in Cellular and Infection Microbiology, 2019)
When transmitted through the oral route, Toxoplasma gondii first interacts with its host at the small intestinal epithelium. This interaction is crucial to controlling initial invasion and replication, as well as shaping the quality of the systemic immune response. It is therefore an attractive target for the design of novel vaccines and adjuvants. However, due to a lack of tractable infection models, we understand surprisingly little about the molecular pathways that govern this interaction. The in vitro culture of small intestinal epithelium as 3D enteroids shows great promise for modelling the epithelial response to infection. However, the enclosed luminal space makes the application of infectious agents to the apical epithelial surface challenging. Here, we have developed three novel enteroid-based techniques for modelling T. gondii infection. In particular, we have adapted enteroid culture protocols to generate collagen-supported epithelial sheets with an exposed apical surface. These cultures retain epithelial polarization, and the presence of fully differentiated epithelial cell populations. They are susceptible to infection with, and support replication of, T. gondii. Using quantitative label-free mass spectrometry, we show that T. gondii infection of the enteroid epithelium is associated with up-regulation of proteins associated with cholesterol metabolism, extracellular exosomes, intermicrovillar adhesion, and cell junctions. Inhibition of host cholesterol and isoprenoid biosynthesis with Atorvastatin resulted in a reduction in parasite load only at higher doses, indicating that de novo synthesis may support, but is not required for, parasite replication. These novel models therefore offer tractable tools for investigating how interactions between T. gondii and the host intestinal epithelium influence the course of infection.